PEMANFAATAN BUAH PEDADA (Sonneratia caseolaris) DALAM PEMBUATAN SELAI - Setiawan, Edi; Efendi, Raswen; Herawati, Netti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Pedada fruit (Sonneratia caseolaris) is one of the complilers of mangrove forest to live along the muddy shore has low salinity and a basin gatherin fire flies. The purpose of this study were to obtain a concentration of sugar and fruit pedada maturity level to quality of jam product. This research used a completely randomized design (CRD) with combination treatment pedada fruit maturity level, percentage increase pedada fruit and the sugar with 6 treatment and 3 replication. From the result of this study showed that the number of maturity level, percentage increase pedada fruit and the sugar significant effect on moisture content, ash content, sucrose content, total acid content, total dissolved solids, descriptive assessment organoleptic and assessment of organoleptic hedonic basis overall. In this study, obtained the best treatment with the moisture content of 26.84%, ash content of 0.31%, sucrose content of 57.82%, total dissolved content of 66.26ºbrix, total acid content of 15.20%, with light green color, in order flavorful pedada, sweet taste and slightly soft texture.     Keyword : Jam, pedada fruit, maturity level, sugar composition.